Is the Episodic Buffer of Baddeley independent of the Central Executive? A new measure of the Episodic Buffer - Vila Chaves, José Óscar; Gutiérrez Martínez, Francisco; García Madruga, Juan Antonio (Anales de Psicología / Annals of Psychology, 2021)
The Episodic Buffer (EB) is taking on an increasingly central role in explanations regarding the functioning of working memory. In fact, in the most recent studies by Baddeley and his collaborators, the EB has situated itself at the core of this memory system. Recently under discussion is that this component of working memory seems to demonstrate an independent nature with respect to central executive resourcing. Some studies show that in automatic tasks the creation and maintenance of elements stored in the episodic buffer do not require resources from the central executive. The current work attempts to evaluate this assumption for what different variables are taken and a new test has been developed to measure the EB. In this double task test, the secondary task consists of reading short simple texts that contain missing words. The results show that further processing due to increasing the length of the texts does not correspond to higher load demands made on the central executive, nor in the creation (organization) of chucks or their maintenance. Thus, we believe the EB is under certain circumstances independent of the central executive.